Marketing 4.0 Strategies to Increase Customer Loyalty with Customer Satisfaction and Customer Decision as Mediators - Made Dewi Prajayanti; Gede Sri Darma (Eduvest - Journal of Universal Studies, 2025)
Customer loyalty will be established if they purchase or use services repeatedly and refer the service to their colleagues. Based on this, the quality of a product and excellent service simultaneously influence customer satisfaction. To achieve this goal, marketing 4.0 is needed. Marketing 4.0 can combine offline and online interactions to make it easier for customers to choose health service facilities. The aim of this research is to determine whether the use of marketing 4.0 can increase customer loyalty with customer satisfaction and customer decisions as a mediator. This type of research is qualytative with a cross-sectional approach. This research was carried out at the Niki Diagnostic Center in Denpasar City, sampling using a purposive sampling method with a total of 110 samples, with data collection through questionnaires and data analysis using Partial Least Square (PLS). The research results show that customer loyalty can be mediated by customer decisions using Marketing 4.0 strategies. It is hoped that future researchers can add other variables to increase customer loyalty.